A One-Pot Synthesis of Oxazepine-Quinazolinone bis-Heterocyclic Scaffolds via Isocyanide-Based Three-Component Reactions - Shaabani, Shabnam; Shaabani, Ahmad; Kucerakova, Monika; Dusek, Michal (Frontiers in Chemistry, 2019)
A novel, efficient and environmentally friendly approach has been developed for the synthesis of biologically important bis-heterocyclic oxazepine-quinazolinone derivatives. The structurally interesting compounds of high purity were synthesized by a one-pot three-component reaction of 2-(2-formylphenoxy)acetic acid and 2-aminobenzamide as bifunctional reagents and an isocyanide without using any catalyst in excellent overall yields.